Population structure, length-weight and length-length relationships, and condition-and form-factors of the pool barb puntius sophore (Hamilton, 1822) (cyprinidae) from the chalan beel, north-central Bangladesh - Mosaddequr . Md Rahman,; Yeamin Hossain, M·d; Abu Sayed Jewel, M·d; MohammadMustafizur Rahman,; Saleha Jasmine,; Elgorban M. Abdallah,; Jun Ohtomi, (Universiti Kebangsaan Malaysia, 2012)
The present study describes the length-frequency distribution, length-weight (LWR) and length-length relationships (LLR), and condition- and form-factors of Puntius sophore wild population from the Chalan beel, north-central Bangladesh. Sampling was done using traditional fishing gears including jhaki jal (cast net), tar jal (square lift net), and dughair (conical trap) during March 2010 to February 2011. For each individual, the total length (TL), fork length (FL) and standard length (SL) were measured by digital slide calipers. Individual body weight (BW) was also taken by a digital balance. A total of 185 specimens ranging from 3.62-9.02 cm TL and 0.70-13.20 g BW were analyzed in this study. The length-frequency distribution showed that the 6-7 cm TL size group was numerically dominant and constituted 43% of the total population. The coefficient b of the LWRs indicated positive allometric growth (b>3.00) for P. sophore in the Chalan beel. The results also indicated that the LWRs were highly correlated (r2 > 0.945). The calculated Fulton’s condition factor (K) values ranged from 0.69-2.35, with a mean value 1.64±0.30. The relative weight (Wr) was not significantly different from 100 for (p=0.074), indicating the balance habitat with food availability relative to the presence of predators for P. sophore. The estimated values of form factor (a3.0) were as 0.0138, 0.0345 and 0.0435 for TL, FL and SL of P. sophore, respectively. These results will be useful for fishery biologists and conservationists to suggest adequate regulations for sustainable fishery management and conservation its numerous stocks in the region